NUMERACY AND LITERACY SKILLS OF JUNIOR HIGH SCHOOL STUDENTS IN RELATION TO MATHEMATICAL ABILITY: A SYSTEMATIC LITERATURE REVIEW - Moulianur Moulianur; Nailul Authary (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2025)
Numeracy literacy is an essential competency that students need to solve contextual problems in everyday life. Various studies indicate that students’ numeracy literacy, particularly at the primary and secondary education levels, still requires improvement. This study aims to systematically review trends in numeracy literacy learning models and examine the relationship between numeracy literacy and students’ self-efficacy. The research employed a Systematic Literature Review(SLR) method consisting of planning, conducting, and reporting stages. Relevant articles were collected from Google Scholar using Publish or Perish software, covering publications from 2020 to 2023 and selected based on predefined inclusion criteria. The results reveal that Problem Based Learning is the most frequently applied learning model to enhance students’ numeracy literacy, followed by Discovery Learning, cooperative learning, and Contextual Teaching and Learning. Furthermore, the findings indicate a positive relationship between numeracy literacy and self-efficacy. Students with higher levels of self-efficacy tend to demonstrate better numeracy literacy skills. In conclusion, the implementation of appropriate learning models and the development of students’ self-efficacy play a significant role in improving numeracy literacy. This study is expected to provide insights for educators and researchers in designing more effective numeracy literacy learning strategies.